Communication between cultures - Samovar, Larry A.; Porter, Richard E. (Wadsworth Publishing, 2007)
Provides an understanding of different cultures and helps students develop practical skills for improving their communication with people from other cultures. This book introduces the study of communication and culture; focuses on the ability of culture to shape our view of reality; and puts the theory of intercultural communication into practice